Subjective lived experience: a resource for coaches' education - Mouchet, A.; Maso, F. (LASE Journal of Sport Science, 2018)
The conceptual contributions of psychophenomenology (Vermersch, 2012) as well as explicitation interviews (Vermersch, 2006) can stimulate debates on reflexive practice and suggest original perspectives in coaches` education. Thus, our aim is to present a `Spiral training approach`, through which research and training can influence each other and become a resource to promote skill development and provide an environment to enhance learning. The coaches` subjective lived experience is at the heart of this analysis, particularly focused on their professional practices and respective transformations. This spiral approach facilitated the analysis of coaches` behaviour who were working within the same team. Furthermore, this multi-method approach included collective training sessions with a group of coaches from the same club. This training approach was employed with rugby union coaches in France, targetting their ability to do half-time speeches during games. Results showed the use and growth of experiential knowledge and effective routines within the technical staff and shared professional knowledge within the club. The effects of the spiral training approach were also analysed with consideration toward the coaches` perceptions and behaviour. We discuss the interest of this approach as an innovative intervention strategy, considering the role of coaches` subjective lived experience in coach education.